(3bjGS GdJHYjI aj GdhWf GdYQHj (B/s - (3GdYjShj, GHQGgjes ((3HjQhJ(B: s (3eQcR OQGSGJ GdhMOI GdYQHjI(B, s, 1989)
(3GdEWGQ GdfXQj(B- (3GdEWGQ GdJWHjbj (B((3eUQ(B- (3GdLRGFQ(B- (3GdSYhOjI(B)-(3eDTQGJ GdYfGUQ GdMGceI dgGeT GdefGhQI(B- (3eDTQGJ GdJHYjI GdEbJUGOjI (B- (3GdJHYjI GdZPGFjI(B- (3GdJHYjI GdKbGajI(B- (3GdJHYjI GdYScQjI(B.s
Keywords: (3GdJHYjIs; (3GdhWf GdYQHjs